Situation report on Nepal’s agrifood systems : June 2023 - Kumar, A.; Kishore, Avinash; Minot, Nicholas; Dorosh, Paul A.; Saroj, Sunil; Koirala, Pankaj; Krupnik, Timothy J. (CSISA, 2023)
Data from May indicates a persistent trend of modest price increases in Nepal. Year-on-year inflation for food and beverage prices was recorded at 5.5 percent, which, though lower compared to 6.9 percent in the previous month and significantly less than in April and May 2022, still denotes an escalation in food prices from an already elevated base. While the high inflation rate impacts all consumers, it is likely to disproportionately strain the finances of the poor, potentially jeopardizing food security. Moreover, the inflation rates for non-food items and services surged to 8.9 percent. The Consumer Price Index (CPI) experienced a somewhat milder increase compared to the Wage Rate Index, registering a 7.4 percent growth as opposed to 7.6 percent. Persistence of high prices for cereals: In April and May of 2023, Nepal did not experience a decrease in staple food prices; instead, there was a slight uptick of 0.5 percent in cereal prices, which were already elevated. In contrast, prices for other food commodities, with the exception of spices, fruits, and milk and eggs, decreased in May 2023. The sustained high prices of staple foods are concerning for the economic well-being of Nepal's poorer households. Agricultural and industrial laborers continued to experience a decline in their real wages: Between April and May, the average wage rates for agricultural and industrial laborers increased marginally by 0.15 percent, whereas the Consumer Price Index (CPI) rose by 1.1 percent during the same period. This indicates a slight decline in real wages. However, wage indices for industrial laborers, such as construction workers, fared better, with increases of 1.0 percent in April and 0.6 percent in May. Consumer price indices depicted spatial variability: In May of 2023, the CPI in the Kathmandu Valley, Terai, Hill, and Mountain rose to 7.7 percent, 7.2 percent, 7.6 percent, and 7.1 percent, respectively. Inflation in these regions was 7.4 percent, 8.2 percent, 7.9 percent, and 8.2 percent during the same period of last year.